2016
DOI: 10.1007/s11064-016-2125-4
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 Attenuates 6-OHDA-Associated Dopaminergic Degeneration in Cellular and Mouse Parkinsonian Models

Abstract: FTY720 (fingolimod) is the first oral drug approved for treating relapsing-remitting forms of multiple sclerosis. It is also protective in other neurological models including ischemia, Alzheimer's disease, Huntington disease and Rett syndrome. However, whether it might protect in a 6-hydroxydopamine (6-OHDA) mouse model associated with the dopaminergic pathology of Parkinson's disease (PD), has not been explored. Therefore, in the present study, we investigated the effects of FTY720 on 6-OHDA-induced neurotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 19 publications
2
42
1
Order By: Relevance
“…Additional work should test this possibility as well as evaluate identified shared microbial markers that correlated with disease in our PD and MSA mouse models. Our results suggest that mice may be useful surrogates for evaluating therapeutic effects on gut function and/or pathology, as we did with FTY720 in parkinsonian A53T Tg mice [22,26,28]. Although here we saw little impact of FTY720 on mouse microbiota, desirable microbial effects were noted in response to FTY720-Mitoxy, supporting further evaluation of this anti-synucleinopathy, neurotrophic-factorenhancing, brain penetrating compound [32,33].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Additional work should test this possibility as well as evaluate identified shared microbial markers that correlated with disease in our PD and MSA mouse models. Our results suggest that mice may be useful surrogates for evaluating therapeutic effects on gut function and/or pathology, as we did with FTY720 in parkinsonian A53T Tg mice [22,26,28]. Although here we saw little impact of FTY720 on mouse microbiota, desirable microbial effects were noted in response to FTY720-Mitoxy, supporting further evaluation of this anti-synucleinopathy, neurotrophic-factorenhancing, brain penetrating compound [32,33].…”
Section: Discussionsupporting
confidence: 65%
“…Previously we and others have studied protection by FTY720, an approved oral immunosuppressive drug for multiple sclerosis, that when phosphorylated acts on sphingosine-1-phosphate receptors (S1P-Rs) [25]. FTY720 causes immunosuppression but also enhances expression of brain derived trophic factor in multiple cell and animal models [26][27][28][29][30]. We showed that FTY720 improves GI physiology/function and reduces GI aSyn pathology in A53T Tg parkinsonian mice [22].…”
Section: Introductionmentioning
confidence: 99%
“…Fingolimod protected dopaminergic markers against the toxicity of 6‐OHDA, rotenone and an acute regimen of MPTP that causes necrotic death of dopaminergic neurons (Ren et al . ; Zhao et al . ; Motyl et al .…”
mentioning
confidence: 99%
“…Our findings are unexpected given three studies published during preparation of this manuscript that found beneficial effects of fingolimod in other toxin-based models of PD. Fingolimod protected dopaminergic markers against the toxicity of 6-OHDA, rotenone and an acute regimen of MPTP that causes necrotic death of dopaminergic neurons (Ren et al 2017;Zhao et al 2017;Motyl et al 2018). In addition, fingolimod reduced a-synuclein pathology in a transgenic mouse model (Vidal-Mart ınez et al, 2016).…”
mentioning
confidence: 99%
“…However, recently, many other animal studies have emerged applying novel oral substances. Ren et al [59] showed that prior administration of fingolimod (FTY720) to 6OHDA-lesioned mice ameliorated motor deficits, dopaminergic neurotoxicity and decreased inflammation. Signalling pathway inhibitors have also been tried.…”
Section: Alternative Immune Therapies For Parkinson 0 S Diseasementioning
confidence: 99%